Analysis of Social Media use as A Parenting Guide by Gen Z - Putri, Lili Dasa; Sunarti, Vevi; Defi, Tri Assifa Candra; Ahmanda, Ritno (Universitas Negeri Padang, 2025)
In the rapidly evolving digital era, social media use has become an integral part of daily life, including for young Gen Z couples. As a generation that grew up with technology, they tend to use social media platforms not only to socialize but also to seek information, including regarding parenting practices within the family. Families, as non-formal educational institutions, provide education through childcare, fostering family empowerment. Social media, with its diverse content, is often the primary source for young couples seeking parenting guidance. This study aims to analyze the use of social media as a parenting guide for young Gen Z couples, focusing on the types of content they consume, its impact on parenting practices, and an evaluation of the quality of the information obtained. This study aims to identify the relationship between the types of social media platforms used and their influence on parenting decisions made by young couples. This research method uses a quantitative approach with a descriptive approach related to social media content. The sample was young Gen Z couples who use social media as a parenting guide in Pariaman City.